PEMBELAJARAN BERBASIS TEACHING FACTORY DI SMK NEGERI 2 SURAKARTA - Rohmah, Wafrotur; Efita Sari, Dhany; Wulansari, Aprilya (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2019)
This study aims to describe preparation process for teaching factory, the implementation of teaching factory, and its evaluation to increase the student’s competency at Vocational High School 2 Surakarta.This is a qualitative research with phenomenology design. The research subjects were principals, vice principals in the curriculum, teaching factory subject teachers and students. Data collection techniques using observation techniques, indepth interviews, and documentation. Data analysis technique with a model in interactive data collection step, data reduction, presentation of data and verification of data/the withdrawal of conclusion. This research result indicates preparation of learning based teaching factory to increase the competency students basically started by putting together lesson plans by teachers teaching factory in the form of soft file and handed it to the field of curriculum. The implementation of learning teaching factory uses the method of learning which he varied, material in the class directions to jobsheet conforming to a standard that is in industry, teachers conditioned practices that done students so that capable of producing quality products put into practice all day skill he would had, the facilities is can be used as well as possible and allocations time provided in accordance with each of their own individual subjects. Evaluation based learning teaching factory done by means of judgment covering the aspects of the discipline attitude, honest, responsibility, tolerance, mutual cooperation, confident, skill and knowledge.